A micro-manipulator vision in IC Manufacturing - Ram Dantu; Dimopoulos, Nikitas; Patel, Rajni; Al-Khalili, Asim (Proceedings. 1988 IEEE International Conference on Robotics and Automation, 1988)
An overview is presented of a micromanipulator vision system for use in automating various functions during the testing of a wafer for semiconducting parameters and inspection of VLSI circuits. Positioning the probe and touching a test pad are the chief concern of the work desired. A brief description of the experimental setup is given. The image processing techniques used in identifying and controlling the location of various components such as the probes and the test pads are discussed. The vision modules and an expert system using hierarchical plan generation to control the sequence of plans are included
Keywords: Automatic testing; Circuit testing; computer vision; computer vision module; computerised pattern recognition; expert system; expert systems; IC Manufacturing; image processing; industrial robots; Inspection; integrated circuit manufacture; integrated circuit testing; Machine vision; Manufacturing; micromanipulator vision; Micromanipulators; Probes; robots; Semiconductivity; Semiconductor device manufacture; Semiconductor device testing; System testing; test pads; VLSI; wafer testing